Evaluasi daur hidup pisang cavendish di Kabupaten Bondowoso: analisis potensi pemanasan global dan alternatif perbaikan - Elida Novita; Ziqrul Oktavian; Idah Andriyani; Ning Puji Lestari (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Cavendish bananas (Musa acuminata Cavendish) have been cultivated in Bondowoso Regency to meet local market demands. Cultivating Cavendish bananas contributes to the potential for emission from global warming (GWP) and environmental quality conditions. This research objective to determine the emission impact and improvement recommendation of Cavendish Bananas production in the Bondowoso Regency as an environmentally friendly product. This research used the Life Cycle Assessment (LCA), which has steps such as goals and scope determining, life cycle inventory, and life cycle impact assessment and interpretations. The results of this research show that in one cycle of Cavendish banana cultivation, total GWP emissions of 95,544 kgCO2eq are generated. This impact is derived from pesticides, chemical fertilizers, diesel fuel consumption, electricity consumption, solid waste, and liquid waste. To minimize these impacts, alternatives such as compost fertilizer, fermented animal feed, processed food from banana hearts, banana chips, wastewater treatment, and the use of solar panels for electricity are needed. If implemented, these alternatives can reduce total GWP emissions by 76% or 72.537 kgCO2eq compared to conventional cultivation.